PERAN SEKTOR PERTANIAN TERHADAP PEREKONOMIAN DI KABUPATEN MIMIKA PROVINSI PAPUA - Isak ., Jawame; Oktavianus ., Porajouw; Grace Adonia Josephine Rumagit (Sam Ratulangi University, 2021)
This research aims to describe the role of the agricultural sector on the economy in Mimika Regency, Papua Province. The type of data used in this study is secondary data, which is data collected by data collection agencies and published to the public. The data analysis used is sectoral contribution analysis, growth rate analysis, and location quotient (LQ) analysis. The results showed that the agricultural sector had no role in the economy of Mimika Regency. The contribution of the agricultural sector in Mimika Regency is low, ranking fifth after the mining, construction, trade, information and communication sectors. The growth of the agricultural sector is also relatively low and tends to decline. Although the LQ value of the agricultural sector is non-basic, it is a strategic sector, especially for the agricultural sub-sector that provides domestic food needs where the agricultural sector also consists of several sub-sectors that directly contribute to boosting the regional economy in Mimika Regency.